2009
DOI: 10.1016/j.expneurol.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Critical age-related loss of cofactors of neuron cytochrome C oxidase reversed by estrogen

Abstract: The mechanistic basis for the correlation between mitochondrial dysfunction and neurodegenerative disease is unclear, but evidence supports involvement of cytochrome C oxidase (CCO) deficits with age. Neurons isolated from the brains of 24 month and 9 month rats and cultured in common conditions provide a model of intrinsic neuronal aging. In situ CCO activity was decreased in 24 month neurons relative to 9 month neurons. Possible CCO-related deficits include holoenzyme activity, cofactor, and substrate. No di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 54 publications
1
29
1
Order By: Relevance
“…Further, fibroblasts isolated from individuals with early onset Parkinson’s disease and mutations in PINK1 were demonstrated to have decreased respiratory capacity related to a decrease in cytochrome c content [29]. Cultured neurons derived from 24 month rat brains appear to have reduced cytochrome c content and complex IV activity when compared with 9 month controls [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Further, fibroblasts isolated from individuals with early onset Parkinson’s disease and mutations in PINK1 were demonstrated to have decreased respiratory capacity related to a decrease in cytochrome c content [29]. Cultured neurons derived from 24 month rat brains appear to have reduced cytochrome c content and complex IV activity when compared with 9 month controls [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several transcriptional and post-translational feedback mechanisms control E2 activity, which likely contributes to the complex dose–response pattern. While the mechanism(s) underlying the reduced ability of ERT to provide cognitive protection with advancing age is unknown, it is known that E2 effects on several biological processes decline with age, including the ability to preserve the blood-brain barrier (Bake and Sohrabji 2004), protect the brain from stroke (Suzuki and others 2009) and neuroinflammation (Benedusi and others 2012), promote growth of glutamatergic synapses (Adams and others 2001; Aenlle and Foster 2010), influence mitochondrial function (Aenlle and Foster 2010; Jones and Brewer 2009), and activate rapid signaling cascades (Fan and others 2010; Foster 2005; Wu and others 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Many potential pathways of energetic failure have been considered [2]. Among these mechanisms are oxidation of nucleic acids [3, 4, 5, 6], calcium dysregulation [7, 8, 9, 10], redox imbalance [11, 12, 13], reactive oxygen species (ROS) attacks [14, 15, 16], and oxidative phosphorylation deficits [17, 18, 19, 20]. Because the availability of energy from oxidative phosphorylation is so critical to neuron function, here, we investigated further the loss of oxidative phosphorylation by controlling the substrate availability to neurons in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Brewer [36] showed that neurons cultured from different ages of rats demonstrate distinct age-related susceptibility to lactate, glutamate, and beta-amyloid. Live neurons isolated from the aging brain environment can be monitored in their endogenous state [17], or permeabilized to allow substrate control and pharmacologic isolation of complexes of the electron transport chain [33]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation